The Strategi Keberlanjutan dan Branding Gula Gending dalam Pelestarian Warisan Gastronomi: Perspektif Kearifan Lokal dan Identitas Budaya: Strategi Keberlanjutan dan Branding Gula Gending dalam Pelestarian Warisan Gastronomi: Perspektif Kearifan Lokal dan Identitas Budaya - Harja, Oktomi; Nirmalasari, Nirmalasari; Rizkiyah, Putri; Ayu Citra Dewi, Gusti; Gabriella Saragih, Vina (Sekolah Tinggi Pariwisata Sahid Surakarta, 2025)
This study examines sustainability and branding strategies in preserving Gula Gending as a form of gastronomic heritage from the perspective of local wisdom and cultural identity. Gula Gending represents a traditional culinary product that reflects cultural values and community-based practices. The study aims to analyze how traditional production processes, branding approaches, and community involvement support heritage preservation within the gastronomy sector. A qualitative method was employed using in-depth interviews, observation, and documentation involving producers and local stakeholders. Data were analyzed descriptively and supported by SWOT analysis to identify internal and external factors influencing branding and sustainability efforts. The findings indicate that authentic production methods, strong cultural narratives, and storytelling-based branding strengthen product identity and perceived value. However, challenges remain related to limited production scale, market access, and brand awareness. This study demonstrates that sustainability-oriented branding can play a strategic role in preserving gastronomic heritage while reinforcing cultural identity and supporting local economic resilience.